OPTIMALISASI MEDIA DIGITAL UNTUK PEMASARAN UMKM: PENGALAMAN PENDAMPINGAN PPM–KKNM INTEGRATIF DI DESA MARGAMEKAR, SUMEDANG - Hasanah, Ferli; Gumilar, Trisna; Subekti, Mega; Septriani, Hilda (Midang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy yet continue to face significant challenges in adopting digital technology for marketing, particularly in non-urban areas. This article reports on a community service program (PPM) conducted under the Integrated PPM–KKNM scheme of Universitas Padjadjaran, aimed at optimizing the use of digital media for MSME marketing in Margamekar Village, South Sumedang District, Sumedang Regency, West Java. The implementation method was participatory and comprised four stages: needs assessment, practice-based training (learning by doing), individual consultation, and technology transfer. Four culinary MSMEs participated as partners: Wening's Catering, Keripik Nufaraz, Kue Basah Bu Neni, and Bakso Margacinta. Results indicate a tangible improvement in partners' digital literacy, evidenced by the establishment of WhatsApp Business accounts, Instagram profiles, and Shopee marketplace stores, as well as the creation of promotional media including business profile videos, product promotion videos, and digital catalogs. The mentoring not only improved marketing communication quality but also expanded market access. These findings affirm that the Integrated PPM–KKNM model, which positions students as field facilitators, is effective in promoting sustainable, locally responsive digital transformation among MSMEs. Keywords: digital literacy, digital media, MSME marketing, Integrated PPM–KKNM, community empowerment